2019
DOI: 10.1029/2019gl084809
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Evaluation of Methods for Maximizing Efficiency and Effectiveness of Hydraulic Fracture Stimulation of Horizontal Wells

Abstract: Hydraulic fracturing enables oil and gas extraction from low‐permeability reservoirs, but there remains a need to reduce the environmental footprint. Resource use, contaminant‐bearing flowback water, and potential for induced seismicity are all scaled by the volume of injected fluid. Furthermore, the greenhouse gas emissions associated with each extracted unit of energy can be decreased by improving resource recovery. To minimize fluid use while maximizing recovery, a rapidly computing model is developed and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…A recent review on the numerical models for hydraulic fracturing can be found in Lecampion et al (2018). Understanding the hydraulic fracture height growth, the interaction with natural fractures and faults, and how to increase the efficiency of hydraulic fractures are the areas of active research (Baykin & Golovin, 2018; Cheng & Bunger, 2019; Flewelling et al, 2013; Ghofrani & Atkinson, 2016; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on the numerical models for hydraulic fracturing can be found in Lecampion et al (2018). Understanding the hydraulic fracture height growth, the interaction with natural fractures and faults, and how to increase the efficiency of hydraulic fractures are the areas of active research (Baykin & Golovin, 2018; Cheng & Bunger, 2019; Flewelling et al, 2013; Ghofrani & Atkinson, 2016; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such a feature plays different roles in geo‐engineering applications. For instance, fracture networks can boost oil/gas extractions in hydraulic fracturing operations (Cheng & Bunger, 2019; Egert et al., 2021; Li & Zhang, 2021; Sanderson & Nixon, 2015); but radionuclides migrate easily within fractures, which brings the performance of deep nuclear waste storage into question (Orellana et al., 2019; Tsang et al., 2015; Viswanathan et al., 2022). Therefore, the evaluation of permeability for fracture networks is pivotal for geo‐engineering.…”
Section: Introductionmentioning
confidence: 99%